OPTIMIZATION OF WIDE-BAND AND WIDE ANGLE CAVITY-BACKED MICROSTRIP PATCH ARRAY USING GENETIC ALGORITHM - Kim, Doo-Soo; Han, Il-Tak; Kim, Woo-Sung; Yang, Jin-Mo; Han, Yong-Hee; Kim, Kyung-Tae (Progress in electromagnetics research M Pier M, 2020)
This paper specifies optimization of a low active reflection coefficient (ARC) array element with a cavity-backed microstrip patch (CBMP) using a genetic algorithm (GA) at wide-band and 2-dimensional (2D) wide angle. Both the GA implemented with a user-defined MATLAB code and a 3-dimensional (3D) full-wave electromagnetic simulator CST MWS are simulated with a real-time direct link. An optimization method using not a traditional unit cell or a small array but a 15 X 15 finite array structure is proposed to apply to a large-scale array antenna. The CBMP array antenna to meet a design goal of a max ARC is optimally designed at equally divided 9 frequencies and 11374 beam angles for S-band 400 MHz operating frequency bandwidth and beam scan coverage (Az = -60[degrees] ~ +60[degrees], El = -3[degrees] ~ +90[degrees]). Measurement results show that a prototype and a full-scale array antenna have low ARC below-8.1 dB and-6.9 dB, respectively for required wide frequency bandwidth and beam scan coverage. It is confirmed that the proposed method is a good solution for optimizing a large-scale array antenna.